ANALYSYS OF PRODUCTION QUALITY, CAPITAL AND LABOR ON THE PRODUCTION OF FLOOR MATTRESSES IN BAURENO DISTRICT BOJONEGORO REGENCY - Happy Adianita; Azhari; Dados Susilowati (Sean Institute, 2022)
This study aims to determine the effect of production quality, capital and labor on the production of floor mattresses in Baureno District, Bojonegoro Regency. This type of research is quantitative using quantitative descriptive associative research methods, for technical data analysis using multiple linear regression, partial correlation analysis, simultaneous, and determinant coefficient (R2). The population in this study were entrepreneurs and workers in Gunungsari Village, 80 respondents were taken as samples using the solvin formula. Collecting data using a questionnaire. From the research that has been carried out, it shows that the variables of production quality, capital, and labor partially have a significant effect on the production of floor mattresses, as evidenced by the results of partial testing that the results of the X1 variable are 0.541 > 0.05, the X2 variable is 0.876 > 0.05, and the variable X2 is 0.876 > 0.05. X3 0.616 > 0.05 means that the independent variable partially has a significant effect. The variables of the quality of raw materials, capital, and labor simultaneously have a significant effect on the production of floor mattresses with simultaneous test results where a value of 0.078 > 0.05 simultaneously has a significant effect on independent variables. And from the research, the coefficient of determination was 62.7%.